THE INFLUENCE OF USER INTERFACE, USER EXPERIANCE AND DIGITAL MARKETING TOWARD PURCHASE INTENTION (STUDY IN SEJASA.COM) - Watulingas, Eldad Baltaszar (Universitas Mercu Buana, 2020)
This study aims to analyze the Effect of User Interface, User Experience and Digital Marketing on Purchase Intention (Study at Sejasa.com). The population in this study was 877 users in Senopati, so the percentage of benefits used was 10% and the results of calculations could have been rounded up to 100 users to achieve the suitability of the study. The sampling method uses Convenience Sampling. Data collection methods using survey methods, with the research instrument is a questionnaire. Measurement of variables is done by Likert Scale. The instrument validity testing is done by correlating the scores on each item with the total score of the respondents' answers. Analysis of the data used is statistical analysis in the form of PLS (Partial Least Square). Research shows that the User Interface (UI) has a negative but significant effect on Purchase Intention, User Experience (UX) has a positive and significant effect on Purchase Intention, and Digital marketing has a positive but not significant effect on Purchase Intention.Â Keywords : Â Â User Interface, User Experience, Digital Marketing, Purchase Intention, Sejasa.com